The mayors of New York - Rozan, S. J. (Rozan, S. J. Lydia Chin/Bill Smith novels, 2023)
When the son of NYC's first female mayor disappears, PI Bill Smith and his partner, Lydia Chin, are called in the find the missing 15-year-old but are faced with more questions than answers, they turn to the only contacts who could help: the neighborhood leaders who are the real "mayors" of NY.